2010
DOI: 10.1590/s2236-89062010000200002
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and comparative analysis of the woody component of a cerrado remnant in Southeastern Brazil

Abstract: -(Community structure and comparative analysis of the woody component of a cerrado remnant in Southeastern Brazil). The aims of the present work were to carry out a floristic-structural study of the shrubby-arboreal component of a savanna fragment (cerrado sensu stricto) in São Paulo State, Southeastern Brazil, and to compare with other areas. Twentyone plots of 250 m² each were delimited and plants with stem basal diameter equal or superior to 3 cm were included in the sampling. The recorded individuals corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…Open grassland (campo limpo, in Portuguese) has a denser herbaceous vegetation with almost any arboreal component when compared to the typical Cerrado (Cerrado sensu stricto, Ribeiro & Walter 2014). Regarding absolute dominance values (the area covered by the transection of all trunks present in the site), the data was similar to the dominance found in some areas of typical Cerrado (Uhlmann et al 1998;Durigan et al 2002;Ishara 2010), although we found lower values than other sites (Toppa 2004;Ishara & Maimoni-Rodella 2010). Absolute density was similar to closed field (campo cerrado, in Portuguese) in Paraná (Uhlmann et al 1998) and typical Cerrado in São Paulo (Durigan et al 2002), and lower than other sites in São Paulo (Ishara 2010;Ishara & Maimoni-Rodella 2010;Carmo et al 2012).…”
Section: Structure Diversity and Similaritysupporting
confidence: 87%
See 3 more Smart Citations
“…Open grassland (campo limpo, in Portuguese) has a denser herbaceous vegetation with almost any arboreal component when compared to the typical Cerrado (Cerrado sensu stricto, Ribeiro & Walter 2014). Regarding absolute dominance values (the area covered by the transection of all trunks present in the site), the data was similar to the dominance found in some areas of typical Cerrado (Uhlmann et al 1998;Durigan et al 2002;Ishara 2010), although we found lower values than other sites (Toppa 2004;Ishara & Maimoni-Rodella 2010). Absolute density was similar to closed field (campo cerrado, in Portuguese) in Paraná (Uhlmann et al 1998) and typical Cerrado in São Paulo (Durigan et al 2002), and lower than other sites in São Paulo (Ishara 2010;Ishara & Maimoni-Rodella 2010;Carmo et al 2012).…”
Section: Structure Diversity and Similaritysupporting
confidence: 87%
“…Regarding absolute dominance values (the area covered by the transection of all trunks present in the site), the data was similar to the dominance found in some areas of typical Cerrado (Uhlmann et al 1998;Durigan et al 2002;Ishara 2010), although we found lower values than other sites (Toppa 2004;Ishara & Maimoni-Rodella 2010). Absolute density was similar to closed field (campo cerrado, in Portuguese) in Paraná (Uhlmann et al 1998) and typical Cerrado in São Paulo (Durigan et al 2002), and lower than other sites in São Paulo (Ishara 2010;Ishara & Maimoni-Rodella 2010;Carmo et al 2012). Most of the sampled individuals were included in the same height class identified in several other studies (Uhlmann et al 1998;Toppa 2004;Ishara 2010;Ishara & Maimoni-Rodella 2010).…”
Section: Structure Diversity and Similaritysupporting
confidence: 87%
See 2 more Smart Citations
“…Within this genus yet another specie Anadenanthera colubrina. Multiple uses of species Anadenanthera have been reported in the literature (Ishara;Maimoni-Rodella, 2010;Cunha et al 2020). The use of bark and seeds have healing action in wound treatment (Pessoa et al 2012;Pessoa et al 2015), antioxidant effect, anti-inflammatory, antimicrobial and use in respiratory diseases (Weber et al 2001;Gama et al 2018).…”
Section: Introductionmentioning
confidence: 99%